Intralymphatic Immunotherapy (ILIT) With Bee Venom Allergens: A Clinical Proof-of-Concept Study and the Very First ILIT in Humans - Chabot, Alexandra; Senti, Gabriela; Erdmann, Iris; Prinz, Bettina M.; Wüthrich, Brunello; Šošić, Lara; Kündig, Thomas M.; Johansen, Pål (Frontiers in Allergy, 2022)
Background Subcutaneous venom immunotherapy (VIT) represents an effective treatment against bee venom allergy. However, it involves long treatment times, high costs, and the risk of adverse events (AEs). Shorter, safer, and cheaper treatment options are therefore pursued. Objective To determine the safety, immunogenicity, and efficacy of bee venom intralymphatic immunotherapy (ILIT). Methods In an open pilot study, 12 patients received bee venom ILIT in three sessions with 14-day intervals: 0.1–5 μg/dose. Ultrasound imaging was applied to guide an injection and to document the lymph node structure. In a second study, 67 patients from 15 centers in Europe and Australia were randomized to receive four doses of either 10- or 20-μg bee venom ILIT with 28-day intervals. Clinical endpoints included specific IgE and IgG and protection after a bee sting challenge. These studies were performed in the years 2000–2003. Results In a proof-of-concept study, no serious AEs were observed. An increase in allergen-specific IgG1 but no IgG4 and IgE was observed. ILIT induced the protection against a bee sting challenge in 7 out of 8 challenged patients. In a multicenter study, an increase in allergen-specific IgG and IgE was observed, with the highest increase in patients receiving a higher ILIT dose. The study was terminated due to several serious AEs upon the sting challenge provocation after the completion of treatment. However, out of 45 patients challenged, 15 (65%) and 18 (82%) patients in the 10- and 20-μg group, respectively, showed an improvement of two grades or more. No correlation was observed between antibody levels and sting protection. Conclusions While a pilot study suggested the safety and efficacy of bee venom ILIT, a high number of AEs seen after the sting challenge following a randomized study indicate that the immunology protection offered by bee venom ILIT is insufficient. Of note, the bee venom allergen extract used in the two studies were from the two different providers. While the first study used a formulation approved for use in subcutaneous VIT, the second study used a nonapproved formulation never tested in humans. Further studies on approved formulations should be performed to generate conclusive results regarding the safety and efficacy of bee venom ILIT.